EFEKTIVITAS USIA KERJA (ASN) BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 DI KABUPATEN GOWA - Haeriah, Haeriah; HL, Rahmatiah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
This article discusses the effectiveness of the working age of state civil servant teachers based on Law number 5 of 2014 concerning state civil servants. This research raises the implementation of the productive age of state civil servant teachers and the efforts made by schools to increase teacher productivity and Islamic legal views regarding the productive age of state civil servant teachers. It is hoped that the regional government will increase the number or appoint teachers with the status of civil servants at this school for the progress of this school and take into account the welfare of its teaching staff and it is hoped that the teaching staff, both civil servants and non-civil servants, will remain trustworthy in carrying out their teaching duties. future future nationals.